The Influence of Professionalism and Personality on Employee Loyalty at the Education and Culture Office of Palu City - Abdul Rahman; Mutmainah; Marwana; Mifriani (Universitas Muhammadiyah Palu, 2023)
This study aims to determine and analyze professionalism and personality simultaneously which have a significant effect on the loyalty of employees of the Palu City Education and Culture Office. And to find out and analyze professionalism and personality partially have a significant effect on the loyalty of employees of the Palu City Education and Culture Office. The research results obtained Fcount = 42.070 at a significant level ÃŽÂ¬ = 0.05 or sig <0.05. From the table shows that the significance value = 0.000. Thus it can be stated that simultaneously (simultaneously) the independent variables have a significant influence on the dependent variable. Professionalism variable, the calculation results show that the regression coefficient value is 0.383, while the significance level is 0.006. So it can be stated that the professionalism variable has a significant and significant effect on employee loyalty at the Education and Culture Office of Palu City. For the personality variable, the calculation results show that the regression coefficient is 0.391, while the significance level is 0.018. So it can be stated that the personality variable has an influence and is significant on employee loyalty at the Education and Culture Office of Palu City.